Psychoeducational Group with Modelling Technique to Improve Career Adaptability Through Career Decision Self-efficacy (Universitas Negeri Semarang, 2019)
This research aimed to examine the effect of psychoeducational group with modelling technique on career decision self-efficacy to improve the career adaptability of the students of State Junior High School 31 (SMP Negeri 31) in Purworejo City. The method used to cover such objective was experimental method with the research design of prettest-posttest control group design. Moreover, there were as many as n2 18 students chosen by using purposive sampling technique among 94 students. Further, based on the data analysis by using bias corrected bootstrapping SPSS 25 with resampling resulted (N = 5.000), while the estimation of the true direct effect was in the level of 95% of confidence interval. This showed that the psychoeducational group with modelling technique contributed direct impact on career adaptability (Î² = 5.61; p < 0.01) as well as indirect impact on career adaptability through self-efficacy (Î² = 7.60, p < 0.05; CI 95% =1.90, 13.86). Through modelling technique, students obtained a picture on the belief of their career direction, abilities, knowledge of their self-potential. They also can plan their future studies which are supported by learning readiness either when they are at school or at home. Based on this research, can prove that strengthening the self-efficacy of career decision would grow up a sense of career expectations conformity which has been possessed and further form the condition of career adaptability so that in the end, one can adapt with their live-span development.